PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KOMITMEN KARYAWAN (Studi Pada PT PLN (Persero) Distribusi Jakarta Raya Periode Mei-Oktober 2016) - Reni Novia (Universitas Mercu Buana, 2017)
The study was designed as an empirical study to test the hypothesis theory and paradigm used is positivistic. The method used in this study is a descriptive analysis method and linear regression analysis. Whereas the test instrument is done through validity and answer the problem given in this research, data are got from 100 employees of PT PLN (Persero) distribution Jakarta, by questionnaires. Some employees being respondent 30-40 years of age, and sex with men are 59%. Result the test data shows that statistical realibility Cronbach’s alpha value above 0,70, so it is considered reliabel, because Cronbach’s Alpha value is above minimum threshold of 0,70. So it can be concluded that the measurement scale organizational culture, working motivation and commitment employees have good realibility. The analysis result shows that organizational culture, working motivation gives positive and significant impact to commitment.Key words : organizational culture, motivation, commitment employees